Leadership Strategic in Facing Non-Military Threat in Indonesia: A Theoritical Review - Savitri, Aida Rahma; Alamsyah, Ruby (PT Hakhara Akademia Indonesia, 2024)
This research aims to analyze strategic leadership in facing non-military threats in Indonesia. The research method used in this research is the library method. The findings from this research are that strategic leadership is leadership with the ability to align the requirements of an organization's external (world) environment with its vision, mission, strategy and organization. An organization's vision describes the future shape of the organization, and an organization's mission describes its core values, goals, and reason for existence. Non-military threats are essentially threats that use non-military factors that can threaten or affect state sovereignty, the territorial integrity of the Republic of Indonesia, and national security.